2016
DOI: 10.1186/s12936-016-1299-1
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum malaria parasitaemia among indigenous Batwa and non-indigenous communities of Kanungu district, Uganda

Abstract: BackgroundThe indigenous Batwa of southwestern Uganda are among the most highly impoverished populations in Uganda, yet there is negligible research on the prevalence of malaria in this population. Plasmodium falciparum malaria parasitaemia prevalence was estimated in an indigenous Batwa and a non-indigenous neighbouring population, and an exploration of modifiable risk factors was carried out to identify potential entry points for intervention. Additionally, evidence of zooprophylaxis was assessed, hypothesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 80 publications
(111 reference statements)
3
33
0
Order By: Relevance
“…The district has an estimated population of 252 100. 13 The Kanungu district is remote with limited infrastructure and service delivery. 13 , 14 Eighty per cent of the population lives in rural settlements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The district has an estimated population of 252 100. 13 The Kanungu district is remote with limited infrastructure and service delivery. 13 , 14 Eighty per cent of the population lives in rural settlements.…”
Section: Introductionmentioning
confidence: 99%
“… 13 The Kanungu district is remote with limited infrastructure and service delivery. 13 , 14 Eighty per cent of the population lives in rural settlements. 15 The majority of the people are of Bakiga ethnicity, while the remainder (~900 individuals) are the indigenous Batwa population who were displaced with the 1993 Bwindi National Park designation.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the importance of primaquine in malaria treatment efforts, the mechanism of primaquine efficacy and haemolytic toxicity are not completely understood [ 4 ]. Recently, a series of studies indicated that primaquine is a pro-drug that is converted to an active metabolite(s) via hepatic metabolism [ 5 13 ]. CYP 2D6 and MAO-A are the key enzymes associated with primaquine metabolism, however, primaquine’s anti-malarial activity is dependent on CYP 2D6-mediated activation [ 6 , 7 , 12 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Community-based cross-sectional surveys were conducted as described in detail elsewhere. 13,14 In April 2014, 136 indigenous Batwa households and 201 non-indigenous Bakiga households were surveyed in the 10 local councils (hereafter referred to as "cells") in Kanungu District, comprising all of Kanungu's 10 Batwa settlements and their neighboring Bakiga villages, resulting in a total of 543 and 731 individuals, respectively. The response rate was 94.9% and 99.4% among the Batwa and Bakiga, respectively.…”
mentioning
confidence: 99%